2016
DOI: 10.3389/fnins.2016.00443
|View full text |Cite
|
Sign up to set email alerts
|

Interference Impacts Working Memory in Mild Cognitive Impairment

Abstract: Mild cognitive impairment (MCI) is considered a transitional stage between healthy aging and dementia, specifically Alzheimer's disease (AD). The most common cognitive impairment of MCI includes episodic memory loss and difficulties in working memory (WM). Interference can deplete WM, and an optimal WM performance requires an effective control of attentional resources between the memoranda and the incoming stimuli. Difficulties in handling interference lead to forgetting. However, the interplay between interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 76 publications
0
12
0
1
Order By: Relevance
“…This was confirmed in subsequent studies (2)(3)(4). Difficulties in inhibitory processes and self-monitoring have also been seen as early features of incipient Alzheimer's disease (AD; [5][6][7][8]. Loewenstein and colleagues (2004) posited that learning deficits are related to deficiencies in the semantic network and found that proactive interference of competing to-be-remembered lists of semantically related targets were especially sensitive to the mild cognitive impairment (MCI) stages of AD (6).…”
Section: Introductionmentioning
confidence: 88%
“…This was confirmed in subsequent studies (2)(3)(4). Difficulties in inhibitory processes and self-monitoring have also been seen as early features of incipient Alzheimer's disease (AD; [5][6][7][8]. Loewenstein and colleagues (2004) posited that learning deficits are related to deficiencies in the semantic network and found that proactive interference of competing to-be-remembered lists of semantically related targets were especially sensitive to the mild cognitive impairment (MCI) stages of AD (6).…”
Section: Introductionmentioning
confidence: 88%
“…And the average annual conversion rate is higher than that of the general population (Petersen et al, 2001). The earliest and most common clinical symptoms of AD are episodic memory loss, accelerated forgetting, and impaired delayed memory (Aurtenetxe et al, 2016). Numerous resting-state functional magnetic resonance imaging (rs-fMRI) studies have shown that there are abnormalities in brain regions and large-scale brain functional networks in MCI and AD patients (Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Problems of effectiveness in resolving interference have also been observed in other populations, such as in people with mild cognitive impairment. Aurtenetxe et al (2016), applying a task similar to that used in the present study, with people with mild cognitive impairment, found that, in the presence of interference -interruption-, there was a greater number of forgotten information. These results are consistent with other inhibition studies with populations with Alzheimer's dementia (Collette, Schmidt, Scherrer, Adam, & Salmon, 2009).…”
Section: Discussionmentioning
confidence: 50%